ANTIMICROBIAL EVALUATION OF SOME HYDRAZONE DERIVATIVES - Jankulovska, M.S., Dimova, V., Doneva-Sapceska, D. (Faculty of Agricultural Sciences and Food - Skopje, 2019)
Hydrazone derivatives represent one of the most active classes of compounds possessing a broad spectrum of biological activity. The use of the hydrazones is due to their anti-inflammatory, antimicrobial, antidepressant, antitumoral, analgesic, antiplatelet, anticonvulsant, antischistosomiasis and antiviral activity. Due to their physiological activity, they are also used in agriculture as herbicides, insecticides, fungicides and plant growth regulators. Furthermore, hydrazone derivatives possessing an azomethine proton (-NH-N=CH-) constitute a significant class of compounds for new drug development in order to synthesize effective agents against microbial activity. Considering these applications some p substituted aromatic hydrazones were previously synthesized and characterized. In this study a series of aromatic hydrazones were evaluated for their in vitro growth and inhibitory activity against Bacillus subtilis, Aspergillus niger and Candida utilis, using filter paper disc method. Stock solutions of compounds were prepared in DMSO, as inert medium in three different concentration levels: 1, 5 and 10 mg/mL. A control disc using DMSO without any test compound was included and there was no inhibitory activity in those disks. The diameter of zone of inhibition (mm) was measured. Every test was done in triplicate to confirm the findings. The screening results indicate that not all investigated compounds exhibited antimicrobial activities. It can be noted that compounds with N-p-methoxy substitute group showed the greatest inhibitory effect against Bacillus subtilis (max zone of inhibition of 14.3 mm) and Candida utilis (max zone of inhibition of 16 mm). All investigated hydrazones showed no inhibitory effects against Aspergillus niger.
Keywords: hydrazones, antimicrobial activity, Bacillus subtilis, Aspergillus niger, Candida utilis.